DIFFERENCE INFLUENCE EXERCISE LOAD METHODS SET AND PYRAMID SYSTEM ON CHANGE HYPERTROPHY OTOT ON MEMBER JETSET FITNESS PALEMBANG - Ponidi Ponidi; Iyakrus Iyakrus; Rostika Flora (Sriwijaya University Learning and Education International Conference, 2018)
This study aims to determine the effect of weight training system set and pyramid system with high motivation and low to muscle hypertrophy changes in members Jetset Fitness Palembang. This research is Quasi experiment research and the design used in this research is Anova 2x2. The population of this study is members of Jetset Fitness amounted to 92 men. Sampling technique using purposive sampling with based on certain characteristics so that the total sample of 40 members. Data collection techniques used questionnaires and tests. The test instrument uses a tape measure with a centimeter unit. Data analysis using spss 20.0 with siginifikansi level of 0.05.The results of the study were: (1) There was a significant influence on pyramid system weight training weight hypertrophy mean 88,100 higher than weight training with set system with mean of 83,750. (2) There is a significant influence on muscle hypertrophy between the set and pyramid system motivation groups F = 4.707 and the significance level of 0.000.(3) There is interaction influence between exercise method and motivation tehadaphypetrophy muscle with Fhitung ≥ Ftabel is 4,707 ≥ 4,01 and level of significance ≤ 0,05 that is 0,036 ≤ 0,05. Conclusion from the result of weight training research of system set and pyramid method that is more effective weight training using pyramid method compared with set system to change muscle hypertrophy.Therefore the authors propose a suggestion for a muscle hypertrophy program can apply weight training using a pyramid system.